Young residents' household waste recycling intentions: Extending TPB through place attachment - Kanishka Pathak; Aditya Yadav; Shivani Sharma; Retu Bhardwaj (Rajagiri Management Journal (RAMJ), 2023)
Purpose - The paper aims to understand the young residents' household waste intentions through place attachment (PA) approach where place dependency (PD) and place identity (PLI) influence recycling intentions (RIs). Furthermore, the effect of norms (both subjective and moral) on residents' association with PLI was also analyzed. Design/methodology/approach - The conceptual model, including the hypothesized relationship between variables, was established through relevant literature. The study extends the theory of planned behavior (TPB) through a place-based approach in young residents' household waste RIs. The proposed conceptual model also replaced the position of norms (subjective and moral) as antecedents to PLI in the proposed extended and modified TPB model. Partial least square structural equation modeling (PLS-SEM) has been used for the statistical analysis of the data. The questionnaires were distributed digitally. The convenience sampling approach was adopted for collecting data. Findings -The results tenably billed the inclusion of placed-based approach in the TPB and norms (subjective and moral) in predicting PLI of young residents. All the alternative hypotheses in the proposed model were accepted. The predictive power of RIs was 41.4%. Research limitations/implications - The research only considered the educated and financially opulent residents, among whom the waste disposal system was well established and may have led to favorable results. The study only limits to measuring intentions, and its organic nature opens vistas for future research studies where more variables could be agglutinated to achieve pronounced prediction power and also further measure actual recycling behavior and practice. Practical implications -The study adds to pragmatic implications for local governments and municipalities where the waste collection apparatuses could capitalize on the findings to achieve efficiency in household waste collection and recycling. Social implications - With young generation of residents at the helm for forging a cleaner environment, the study motivates environmental enthusiasts and social scientists to better understand household waste RIs. The study will help young generation to become more sensitized towards the environment by making green changes in daily disposal habits. Originality/value - The study explored two prospects. First, PA (place dependence and place identity) was added as an external variable and precedent to RIs, and second, the norms (both subjective and moral) were taken as antecedents to place identity.
Keywords: 650; Household waste; Recycling intentions; Place attachment; Theory of planned behavior; Norms; Young residents